Judgment accuracy of German student texts: Do teacher experience and content knowledge matter?. (November 2022) - Möller, Jens; Jansen, Thorben; Fleckenstein, Johanna; Machts, Nils; Meyer, Jennifer; Reble, Raja
Abstract: The central purpose of our study is to analyze whether teacher experience and content knowledge relate to teacher judgments on student report texts. Ninety-one experienced teachers, including 27 specializing in the subject of the German language, and 136 teacher students, including 37 majoring in German Studies, participated in this study. Participants assessed ten randomly selected authentic student reports from ninth graders. Experienced teachers revealed a lower absolute judgment accuracy revealing stricter and more heterogeneous judgments than teacher students and specially trained experts. However, relative judgment accuracy (correlation between teachers' and experts' judgments) was higher when teachers majored in German Studies. Highlights: Examining teacher judgment accuracy when assessing authentic students' report texts on a digital platform. Experienced teachers judged stricter and more heterogeneous than teacher students and experts in a German context. Majoring in German Studies leads to a higher rank component when assessing German texts.